Low health literacy and healthcare utilization among immigrants and non-immigrants in Switzerland. Issue 11 (November 2017) - Mantwill, Sarah; Schulz, Peter J.
Highlights: Functional health literacy is associated with knowledge on healthcare utilization. (Micro-)cultural differences are independent predictors of utilization. Different health literacy measures are not equally associated with utilization. Abstract: Objective: This study aimed at investigating the association between functional health literacy and knowledge on when to seek medical help for potentially harmless (overutilization) or serious (underutilization) situations among immigrants and non-immigrants in Switzerland. Methods: Data was collected among three immigrant groups and the native population ( N = 1146) in the German- and Italian-speaking part of Switzerland. Health literacy was assessed with the Short Test of Functional Health Literacy (S-TOFHLA) and three Brief Health Literacy Screeners. Over- and underutilization of healthcare services was assessed with items asking participants about when to seek medical help for minor, respectively major, physical symptoms. Results: Immigrants were more likely to seek medical help when unwarranted (overutilization). Health literacy, when assessed with the S-TOFHLA, was significantly associated with over- and underutilization. Yet, once controlled for covariates, the association between health literacy and overutilization was negative. Immigration background and micro-cultural differences emerged as important predictors of utilization. Conclusions: Results suggest that functional health literacy is directly related to healthcare utilization. The effects might be amplified by (micro-)cultural differences. Practice implications: Healthcare providers should be aware of differences in health literacy and utilization patterns among different population groups. Communication between patients and providers should be literacy and culturally sensitive.